Assessment of Dental Caries Predictors in a Seven-year Longitudinal Study - Elaine Pereira da Silva Tagliaferro, DDS, MSc; Antonio Carlos Pereira, DDS, MPH, DrPH (Blackwell Synergy, 2006)
To identify, in a group of 6-8-year-old schoolchildren, risk factors for dental caries increment in permanent dentition.